STOCK PRICE BEHAVIOR AROUND CUM-DIVIDEND DATE OF INDONESIA BLUE CHIPS STOCKS - Lavista, Eka (Review of Management and Entrepreneurship, 2019)
This study tests whether there are significant stock prices changes around the cum-dividend date. In particular, it examines the stock price movement of two days before and two days after the cum-dividend date. It uses an event study methodology. The population of this study are all companies in the LQ45 listed at Indonesia stock exchange for the year 2017 and the sample consists of 38 companies. Abnormal return is measured using the single index model. Results show that there are no significant abnormal returns around the cum-dividend date. In addition, there is no significant abnormal return difference between two days before and two days after the cum-dividend date. The implication of the reported findings is that investors may not obtain significant positive abnormal returns using a cum-dividend date as the trading strategy.